Effect of the nanoformulation of siRNA-lipid assemblies on their cellular uptake and immune stimulation - Kubota K (Dove Medical Press, 2017)
Kohei Kubota,1,2 Kohei Onishi,3 Kazuaki Sawaki,3 Tianshu Li,4 Kaoru Mitsuoka,5 Takaaki Sato,6 Shinji Takeoka1,3,4 1Cooperative Major in Advanced Biomedical Sciences, Graduate School of Advanced Sciences and Engineering, Waseda University (TWIns), Tokyo, Japan; 2Formulation Research and Phramaceutical Process Group, CMC R&D Center, Kyowa Hakko Kirin Co., Ltd, Shizuoka, Japan; 3Department of Life Science and Medical Bioscience, Graduate School of Advanced Science and Engineering,Waseda University (TWIns), Tokyo, Japan; 4Research Organization for Nano and Life Innovation, Waseda University (TWIns), Tokyo, Japan; 5Research Center for Ultra-High Voltage Electron Microscopy, Osaka University, Osaka, Japan; 6Department of Chemistry and Materials, Faculty of Textile Science and Technology, Shinshu University, Nagano, Japan Abstract: Two lipid-based nanoformulations have been used to date in clinical studies: lipoplexes and lipid nanoparticles (LNPs). In this study, we prepared small interfering RNA (siRNA)-loaded carriers using lipid components of the same composition to form molecular assemblies of differing structures, and evaluated the impact of structure on cellular uptake and immune stimulation. Lipoplexes are electrostatic complexes formed by mixing preformed cationic lipid liposomes with anionic siRNA in an aqueous environment, whereas LNPs are nanoparticles embedding siRNA prepared by mixing an alcoholic lipid solution with an aqueous siRNA solution in one step. Although the physicochemical properties of lipoplexes and LNPs were similar except for small increases in apparent size of lipoplexes and zeta potential of LNPs, siRNA uptake efficiency of LNPs was significantly higher than that of lipoplexes. Furthermore, in the case of LNPs, both siRNA and lipid were effectively incorporated into cells in a co-assembled state; however, in the case of lipoplexes, the amount of siRNA internalized into cells was small in comparison with lipid. siRNAs in lipoplexes were thought to be more likely to localize on the particle surface and thereby undergo dissociation into the medium. Inflammatory cytokine responses also appeared to differ between lipoplexes and LNPs. For tumor necrosis factor-α, release was mainly caused by siRNA. On the other hand, the release of interleukin-1β was mainly due to the cationic nature of particles. LNPs released lower amounts of tumor necrosis factor-α and interleukin-1β than lipoplexes and were thus considered to be better tolerated with respect to cytokine release. In conclusion, siRNA-loaded nanoformulations effect their cellular uptake and immune stimulation in a manner that depends on the structure of the molecular assembly; therefore, nanoformulations should be optimized before extending studies into the in vivo environment. Keywords: nanoformulation, siRNA, cryo-TEM, confocal microscopy, endocytosis, immune stimulation